Developing a patient-centered outcome measure for complementary and alternative medicine therapies II: Refining content validity through cognitive interviews - Thompson, Jennifer J (BioMed Central, 2011)
BACKGROUND: Available measures of patient-reported outcomes for complementary and alternative medicine (CAM) inadequately capture the range of patient-reported treatment effects. The Self-Assessment of Change questionnaire was developed to measure multi-dimensional shifts in well-being for CAM users. With content derived from patient narratives, items were subsequently focused through interviews on a new cohort of participants. Here we present the development of the final version in which the content and format is refined through cognitive interviews. METHODS: We conducted cognitive interviews across five iterations of questionnaire refinement with a culturally diverse sample of 28 CAM users. In each iteration, participant critiques were used to revise the questionnaire, which was then re-tested in subsequent rounds of cognitive interviews. Following all five iterations, transcripts of cognitive interviews were systematically coded and analyzed to examine participants' understanding of the format and content of the final questionnaire. Based on this data, we established summary descriptions and selected exemplar quotations for each word pair on the final questionnaire. RESULTS: The final version of the Self-Assessment of Change questionnaire (SAC) includes 16 word pairs, nine of which remained unchanged from the original draft. Participants consistently said that these stable word pairs represented opposite ends of the same domain of experience and the meanings of these terms were stable across the participant pool. Five pairs underwent revision and two word pairs were added. Four word pairs were eliminated for redundancy or because participants did not agree on the meaning of the terms. Cognitive interviews indicate that participants understood the format of the questionnaire and considered each word pair to represent opposite poles of a shared domain of experience. CONCLUSIONS: We have placed lay language and direct experience at the center of questionnaire revision and refinement. In so doing, we provide an innovative model for the development of truly patient-centered outcome measures. Although this instrument was designed and tested in a CAM-specific population, it may be useful in assessing multi-dimensional shifts in well-being across a broader patient population.